HOW TO PLAY AND TUNE SASANDO IN EDON STYLE - MARIA KLARA AMARILIS CITRA SINTA DEWI TUKAN; FLORA CEUNFIN; MELKIOR KIAN (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2020)
Sasando is one of the cultural artifacts of the Rote Tribe that was born from ideas, good values, and local wisdom of the Rote people. This research is a qualitative case study type research aimed at gaining an understanding of sasando plays in Edon Studio and its tuning techniques. Edon Studio chose because the Edon technique has the characteristic of only using 7 fingers to play sasando and being able to tune sasando with two scales simultaneously. The results showed that at Edon Studio, sasando was played using 7 fingers consisting of 4 fingers of the left hand and 3 fingers of the right hand. On the left hand, the thumb and index finger enter in playing the melody, while the middle finger and ring finger meet in playing the bass. Besides playing the melody, the index finger is more positioned as the center of the movement of the other fingers. On the right hand, the thumb, index finger and middle finger are used to play rhythm. The middle finger meets as the commander, while the thumb and index finger meet to form the chord. For chords consisting of four notes, for example C7 chords, one note can be played from the melody (left hand). Regarding tuning, at Edon Studio, sasando tuning is done by considering modulation, namely sasando tuned using two scales. To set two or more basic sasando tunes, three important steps are used, namely: a) analyzing the composition of the melody on the song that will be played